Diagnostic and Management Pathways for Pulmonary Carcinoid Tumours in the United Kingdom: Results from the National Lung Neuroendocrine Tumour Pathway Project - Wasat Mansoor; Stuart Ferguson; Victoria Ross; Denis Talbot (International Journal of Endocrinology)
There is inconsistency among published guidelines for the optimal diagnostic and management pathways for patients with typical (TC) or atypical (AC) pulmonary carcinoid tumours. We conducted a UK-wide clinician survey to assess current practice for the diagnosis, management, and follow-up of patients with TC/AC and descriptively compared management between European Neuroendocrine Tumor Society (ENETS) accredited centres of excellence (CoE) and nonaccredited centres (non-CoE). Twenty-seven clinicians (10 CoE; 17 non-CoE) participated. Computed tomography of thorax, abdomen, and pelvis was the most commonly reported diagnostic tool (96% of respondents), and bone scans and gallium somatostatin receptor scintigraphy positron emission tomography (SRS PET) were the least commonly reported (30% and 37% of respondents, respectively). Adjuvant therapy is considered for resected TC/AC by <5% of respondents for patients with stage N0 M0 AC or TC, up to 48% of respondents for patients with AC with R1 disease. Somatostatin analogues were the most commonly reported first-line treatment (63% of respondents), and chemotherapy was the most commonly reported second-line therapy and third-line therapy (33% and 41%, respectively) for unresectable and metastatic disease. Reported frequency of initial follow-up after primary surgery ranged from every 2 months to annual, and total follow-up duration ranged from 2 years to indefinite depending on disease type (TC/AC) and stage. For most diagnostic investigations, the highest reported frequency of use was in CoE, most notably gallium SRS PET (70% CoE vs. 18% non-CoE respondents). 93% of respondents (100% CoE; 88% non-CoE) reported having neuroendocrine tumour- (NET-) specialist multidisciplinary team meetings at their centre; 59% (90% CoE; 41% non-CoE) had a NET Clinical Nurse Specialist (CNS) and 48% (80% CoE; 29% non-CoE) had a lung NET patient database. The survey results suggest variability between UK centres in diagnostic pathways and management of patients with TC/AC and suggest that CoE may be able to offer an improved service to patients.